2019
DOI: 10.1039/c9en00348g
|View full text |Cite
|
Sign up to set email alerts
|

Surface coating effects on the sorption and dissolution of ZnO nanoparticles in soil

Abstract: Soil pH and dissolved organic matter (DOM) content are among the most important factors affecting the bioavailability of Zn and the binding and dissolution of ZnO nanoparticles (NPs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…The larger zeta potential values represent a lower degree of aggregation that leads to a higher degree of stability of nanoparticles and a smaller zaveraged hydrodynamic diameter. At lower zeta values, the nanoparticles flocculate early and the stability of the nano-suspension reduces [44]. The Zeta potential of ZnONPsin the present study was -24.0 mV, which provided evidence that the fabricated nanoparticles were moderately stable, which led to the monodispersity of the particles.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The larger zeta potential values represent a lower degree of aggregation that leads to a higher degree of stability of nanoparticles and a smaller zaveraged hydrodynamic diameter. At lower zeta values, the nanoparticles flocculate early and the stability of the nano-suspension reduces [44]. The Zeta potential of ZnONPsin the present study was -24.0 mV, which provided evidence that the fabricated nanoparticles were moderately stable, which led to the monodispersity of the particles.…”
Section: Discussionsupporting
confidence: 50%
“…The magnitude of the Zeta potential (−30 mV to +30 mV) indicates the potential stability of the colloidal system [44][45][46]. The Zeta potential is related to the nanoparticles' stability in the solution.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported that NPs exhibit sorption on exchange sites and that soil parameters largely affect their behavior in the soil by regulating the sorption, dissolution, and aggregation processes (Carbone et al 2016;Baddar et al 2019) or by modifying particle surface properties, which may alter Zn availability to plants (De Santiago-Martin et al 2015;Meesters et al 2019). The high reactivity of metalbased NPs resulting from their large surface areas and small sizes could cause their aggregation to similar NPs (homoaggregation) and to natural colloids, which are also present in pore water (hetero-aggregation).…”
Section: Comparison Between Soil Zn Extractability and Zn Bioaccumulation In Plantmentioning
confidence: 99%
“…Plant responses to metallic and metal oxide NPs vary greatly with plant species (and even ecotypes), growth stages, soil properties, application methods, doses, and durations of NP exposure, as well as the specific surface area and size-related properties of NPs (Ebbs et al 2016;Kopittke et al 2019;Poynton et al 2019;Su et al 2019;Tortella et al 2019;Meesters et al 2019). The interactions of NPs with different soil components have a profound impact on their fate, transport, and behavior (Mitrano et al 2017;El Hadri et al 2018;Baddar et al 2019;Zhao et al 2019). Natural soils exhibit broader particle size distributions, more irregular grain shapes, greater variations in surface charge, and a larger variety of mineral surface types than synthetic culture media.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, aggregation and dispersion of pristine silver (Ag) NPs suspended in natural organic matter (NOM) solution [3] and dissolution of zinc oxide NPs in soil [4] are highly capping agent dependent. Information on organic capping agents is relevant in the context of material development and synthesis, risk assessment [5,6] and biomedical applications [7].…”
Section: Introductionmentioning
confidence: 99%